MILITARY OPERATIONS OF THE KURDISTAN DEMOCRATIC PARTY ORGANIZATIONS IN DUHOK CITY BEFORE THE MARCH 1991 UPRISING - Ahmed, Hayam (Humanities Journal of University of Zakho, 2026)
This study sheds light on a marginalized and undocumented stage of the Kurdish liberation movement in Duhok, focusing specifically on the period preceding the March 1991 uprising. Despite its pivotal importance in the trajectory of Kurdish resistance, this phase has received little attention in academic research, journalistic coverage, or previous literature. The research examines how activists managed to break the wall of fear imposed by the Ba’athist regime on the population for decades and revive popular consciousness after a forced dormancy caused by systematic repression and genocidal policies against Kurdish society. The study adopts a socio-historical methodology, relying on direct field testimonies and an in-depth analysis of participants’ narratives and eyewitness accounts of key clandestine operations during that era, such as the bombing of Al-Kifah (Bzaf) School in February 1991 and the attempted attack by the Broshki unit in March of the same year. The findings reveal that these operations were not merely isolated military incidents but strategic turning points that helped rebuild trust between society and the revolutionary factions, paving the way for mass mobilization that culminated in the uprising. Although these efforts did not achieve full military success, they left a profound psychological and symbolic impact, reaffirming that the Kurdish will for liberation remained unbreakable and that the spirit of resistance continued to burn strongly in the collective consciousness of Duhok’s people. Which makes that period a clear indication of the strength of Kurdish national identity, its historical persistence against the policies of erasure and genocide that targeted it.